Analisis Kepuasan Pelayanan Dekanat Berdasarkan Pengalaman Mahasiswa Fisip Universitas Sriwijaya - Wati, Desi Kurnia; Ramadhani, Reviantika; Ardi, Rorencia Azzahra; Putria, Meilani; Mutmainah, Nur Afny (@-Publik: Jurnal Administrasi Publik, 2025)
Quality administrative services in higher education play a crucial role in supporting the smooth academic process for students. At the Faculty of Social and Political Sciences (FISIP) of Sriwijaya University, administrative services at the dean's office have received positive feedback from students, who find the procedures efficient, quick, and easy to understand, making it easier for them to complete their academic tasks. Research by Neka Nopiyanti, Sriati, and Katriza Imania (2024) shows that dimensions such as reliability, assurance, and empathy play a significant role in enhancing student satisfaction. Interviews with students also revealed that the dean's office staff are not only quick and professional but also show friendly and patient attitudes, even when dealing with long queues. This responsive and attentive service creates an academic environment that supports student success. Therefore, quality administrative services at FISIP UNSRI play a vital role in supporting students' academic success and fostering a conducive learning environment on campus.